Detection of Clarithromycin Resistance Genes of Helicobacter Pylori and Treatment Outcomes of Alternative Regimens among Yemeni Patients at the University of Science and Technology Hospital, Sana’a City - Al-Baidhani, Entesar Saleh Abobakr Amer (University of Science and Technology, Sana’a, 2026)
Helicobacter pylori (H. pylori) is a common bacterium infecting about half of the world's population, with even higher rates in developing countries. This bacterium is considered the main reason for gastritis and peptic ulcers. Many of its strains are becoming resistant to antibiotics, especially clarithromycin, making treatment more challenging. This resistance can lead to serious health issues, including gastric cancer. This study aimed to identify clarithromycin-resistant mutations in H. pylori strains and the impact of alternative regimens in Yemeni patients at the University of Science and Technology Hospital in Sana’a City. A prospective study was conducted on 116 patients using gastric biopsy samples and employed molecular techniques, particularly quantitative polymerase chain reaction PCR, to detect specific mutations in the 23S rRNA gene linked to clarithromycin resistance. Patients with mutations were followed up after receiving alternative antibiotics, levofloxacin triple therapy, and bismuth quadruple therapy. In this study, the results showed a significant prevalence of clarithromycin-resistant H. pylori strains among the patients (41.2%). The most common mutation was A2143G (61.5%), followed by A2142G (19.2%), A2142C (15.4%), and a double mutation A2143G-A2142G (3.8%). Samples with wild-mutant genes were observed in 7.7%. After interventions were performed using alternative eradication regimens, the eradication rates of levofloxacin triple therapy and bismuth quadruple therapy were 84.2% and 77.8%, respectively. Additionally, phenotypic resistance to clarithromycin was 38.7%. The findings of this study indicate an increase in resistance to clarithromycin in H. pylori strains among Yemeni patients, which highlights the urgent need for regular molecular testing to guide treatment decisions. Understanding the genetic mutations behind this resistance is essential for improving patient care and lowering the risk of severe complications related to H. pylori infections.
Keywords: Clarithromycin Resistance Genes; Helicobacter Pylori; Alternative Regimens; PharmacologyPharmacologyPharmacologyPharmacologyPharmacologyPharmacology; Yemen